Global Labour Journal (Global Labour Journal, 2010)
This online, open access, academic journal serves as a forum to capture the plentiful and diverse scholarly work emerging on labour activities worldwide, with the aim of understanding, recording, and promoting the transition of the labour movement to a new form of global unionism, and highlighting the ways labour activities are increasingly shaped by global forces. Global Labour serves the labour studies community by soliciting academic work on a wide variety of workers and worker related issues. These range from single country to comparative to international studies of workers and their organizations in the areas of the global North and South. We are especially interested in receiving submissions from regions of the world that are often neglected in labour studies. A key area of focus is the informal sector of labour, and the accompanying shift of focus away from the traditional ‘workplace’ as well as ‘traditional workers’ as the central locus of action. Other key areas of inquiry are migration; peasant agriculture and the transition to mass agriculture; and the impact of new multilateral institutions on global labour activities. The journal also solicits articles that represent the diversity of labour identities and emergent labour strategies, forms and organization. This includes corporate restructuring, traditional trade union responses, labour service organizations, new social movements, as well as the conventional institutions that workers engage in the workplace such as works councils, sector wide bargaining institutions, institutions that mediate conflict and political parties that have links with labour. The journal seeks to explore the role of globalization in breaking down boundaries between the global/local and the public/private as they relate to labour activities. The journal does not espouse a particular political line in labour studies, but welcomes a wide variety of approaches and analysis. Our aim is to provide a global forum for scholarly work on a comparative sociology of the labour movement. --Website description